Mobile health in the prevention and detection of cardiovascular diseases (2022)
The document presented was the initial design and investigation for a mobile app development that aims to prevent and detect cardiovascular disease risk in the adult population of Colombia. Currently this works is still undergoing with researchers from the Department of Biomedical Engineering , Department of Systems and Computing Engineering and La Cardio